Experimental restoration treatments for burn pile fire scars in conifer forests of the Front Range, Colorado - Shanklin, Amber, author; Paschke, Mark, advisor; Rhoades, Charles, advisor; Stromberger, Mary, committee member (Colorado State University. Libraries, 2014)
Drastic changes in soil physical, chemical, and biotic properties following slash pile burning and their lasting effects on vegetation cover have been well documented in ecosystems worldwide. However, processes that inhibit burn scar recovery are poorly understood as are the means for their rehabilitation. This study compared plant and soil responses to a number of surface treatments designed to alter microclimate, moisture infiltration, and nutrient status of recently burned slash piles along the Front Range of Colorado. Hand-applied surface manipulation treatments including: scarification, woodchip mulch, and tree branch mulch were compared with untreated burn scars, both with and without addition of a native species seed mix at 19 sites. Pile burning effects were observed by comparing fire scar centers with unburned reference areas while restoration treatment effectiveness was observed by comparing treated scar centers with untreated scar centers. I found surface manipulations had little effect on vegetation recovery while seeding scars increased total plant biomass significantly. Woodchip mulch consistently increased soil moisture, decreased inorganic nitrogen availability, and inhibited plant regrowth in scars. Branch mulch and soil scarification showed no effect on plant regrowth and little effect on soil physical and chemical properties. Non-native species did not have a significant presence within slash scars and were no more prevalent in fire scar centers than reference conditions (unburned areas). Recommendations based upon results of this study include seeding native species in fire scars to promote native species reestablishment.
Keywords: restoration; fire scar; slash piles